Implementasi Prinsip Due Diligence dalam Kewajiban Negara Mencegah Cyber Attacks: Tinjauan Hukum Internasional Kontemporer - Berliant Pratiwi; Neilin Nikhlis (Universitas Sains dan Teknologi Komputer, 2026)
The rapid evolution of cyberspace has transformed it into a strategic domain of international relations, raising complex legal challenges regarding state responsibility for preventing cross-border cyberattacks. This study explores the implementation of the due diligence principle in international law as a normative foundation for evaluating a state’s obligation to prevent harmful cyber activities originating from its territory. Utilizing a normative-legal approach, the research analyzes global legal instruments, state practices, and Indonesia’s position on due diligence. Findings reveal a significant gap between the doctrinal recognition of due diligence and its operational application, especially in developing countries lacking institutional and regulatory capacity. The study proposes practical recommendations for integrating due diligence into national Cybersecurity strategies while contributing to the broader development of binding international cyber norms. By focusing on Indonesia, the research aims to strengthen both national legal preparedness and its international legal standing in cyberspace governance.